Langerhans cell histiocytosis of single‐system multifocal bone, including the mandible, in a 22‐month‐old child: A case report. Issue 1 (5th June 2022) - Sakai, Kiyoshi; Yamamoto, Noriyuki; Yamaguchi, Satoshi; Okabe, Kazuto; Koma, Yoshiro; Hibi, Hideharu
Abstract: Background: Langerhans cell histiocytosis (LCH) is a rare disease in which antigen‐presenting Langerhans cells proliferate abnormally. Case Presentation: We report a case of a 22‐month‐old boy who presented with left cheek swelling. A palpable bony bulge was noted at the left mandibular angle and a malignant tumor was suspected. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed an area of bone resorption from the left mandibular angle to the mandibular branch. Positron emission tomography (PET)‐CT revealed accumulation in the left mandible, left femoral diaphysis, and L1 vertebra. The patient was diagnosed with multiple‐bone LCH and underwent chemotherapy. Conclusion: Four years after treatment, the patient is doing well and has no recurrence.